Enhancing pollutant removal in constructed wetlands by Anodonta woodiana: The role of bioturbation driven microbial community restructuring - Fangshu Wang; Yingzi Ma; Shuo Li; Guosheng Wang; Jicheng Duan; Xiaowan Dong; Shuoyang Wang; Qingyang Bi; Dong Chen (Journal of Water Process Engineering, 2026)

Proximal-distal coordination engineering of iron single-atom nanozyme for synergistic multi-enzymatic-photothermal control of antibiotic-resistant bacteria - Yunsen Wang; Zhichao Yu; Xiuhui Liang; Zhilan Bi; Minglang Zou; Shuo Tian; Da Huang; Zuquan Weng; Dianping Tang; Jinfeng Kong (Journal of Hazardous Materials, 2026)

Triple-responsive supramolecular hydrogel with synergistic photothermal effect regulates inflammatory signaling to remodel the diabetic wound microenvironment and promote chronic wound healing - Jishang Sun; Jingwen Wang; Junfeng Ai; Ruxin Wang; Yanru Diao; Baoqin Han; Qingqing Bi; Jing Chang; Shuo Wang (Chemical Engineering Journal, 2026)

Vesicle3D: An Integrative Platform for 3D Segmentation and Analysis of Vesicles in Cryo-electron Tomograms - Zheng-Yu Lv; Zhen-Hang Lu; Shuo Liu; Pengcheng Zhou; Pak-Ming Lau; Guo-Qiang Bi; Chang-Lu Tao (Neuroscience Bulletin, 2026)

Efficient hydrolysis of glycosides by Pichia kudriavzevii with high-activity β-glucosidase: a critical role in enhancing terpene aroma in beer - Lin Yuan; Xiaoping Hou; Yang He; Xiujuan Wan; Jiaxin Han; Wenqi Xu; Shuo Yu; Shuang Bi; Lijuan Ma; Lei Xing (Food Chemistry, 2026)

Nitrogen‐Driven Acidification and Microbial Shifts Contribute to a Breakdown in Carbon–Phosphorus Trade in the Rhizosphere - Shuo Sun; Ruzhen Wang; Jordi Sardans; Mengjiao Bi; Ying Zhang; Xinyu Fan; Xiaoyu Guan; Yong Jiang; Mingkai Jiang; Xingguo Han; Josep Peñuelas (Global Change Biology, 2026)
Anthropogenic nitrogen (N) deposition is reshaping terrestrial phosphorus (P) cycling. This effect is pronounced in the rhizosphere, where plants respond to P status by releasing root exudates. Yet it remains unclear whether these interactions drive P mobilization or immobilization. To capture both the chronic effects of N deposition and the transient effects of root exudates, we integrated a decade‐long N addition experiment (a single annual application of (NH 4 ) 2 SO 4 at 0, 2, and 5 g N m −2 year −1 ) with a 14‐day laboratory incubation. Specifically, rhizosphere and bulk soils from a Eurasian meadow steppe were amended with 13 C‐labeled low‐molecular‐weight organic acids (LMWOA; a single addition of acetic and succinic acids). Phosphorus transformation was quantified using sequential extraction and 31 P NMR, while underlying mechanisms were assessed via priming effects, phosphatase activity, and microbial functional genes. Nitrogen enrichment promoted the dissolution of mineral‐bound inorganic P (P i ) through acidification (pH drop > 1 unit), leading to the accumulation of secondary mineral P i and organic P (P o ). This was accompanied by reduced microbial phosphatase activity and lower abundances of the P‐cycling genes phoC and phoD . The above effects were stronger in the rhizosphere than in bulk soil. In the rhizosphere, LMWOA enhanced microbial P immobilization and P o accumulation, even as their positive priming effects accelerated soil organic carbon mineralization. These results were partly driven by the recruitment of key P‐cycling taxa such as Burkholderia and Rhodoplanes , suggesting a shift in carbon‐for‐P exchange between plants and microbes under N deposition. Collectively, our findings indicated that while N‐induced P solubilization may temporarily alleviate P limitation, synergy with increased LMWOA exudation promotes P o accumulation. Though P o can be labile compared to mineral‐bound forms, suppressed phosphatase activity likely constrains its mineralization. This inhibition potentially decelerates P cycling, thereby compromising the medium‐ to long‐term P supply within the Eurasian steppe.

Subcellular Structures in Native Hippocampal Synapses Revealed by Cryo-electron Tomography - Chong-Li Tian; Lei Qi; Zhen-Hang Lu; Shuo Liu; Min-Ling Gu; Wen-Lan Huang; Yi-Tong Yan; Yun-Tao Liu; Jing Wu; Peiyi Wang; Z. Hong Zhou; Guo-Qiang Bi; et al. (Neuroscience Bulletin, 2026)

Spallation of underground rock openings with weak planes in surrounding rock mass subjected to dynamic loading: An analytical investigation - Yao Wang; Zhiyi Liao; Weiyue Bao; Shuo Bi; Jianbo Zhu (Tunnelling and Underground Space Technology, 2026)

River remediation driven by micro-nano bubbles: From laboratory verification to in situ application - Fangshu Wang; Wen Yang; Shuo Li; Guosheng Wang; Dongmei Wang; Jicheng Duan; Jianyong Feng; Xiaowan Dong; Shuoyang Wang; Qingyang Bi; Dong Chen (Journal of Environmental Chemical Engineering, 2026)

Analysis of the efficient and stable organic matter removal performance and microbial community in a two-stage A/O-MBBR pilot-scale system - Shuo Li; Xiaowan Dong; Juntao Cheng; Fangshu Wang; Liyan Wang; Xifeng Zhao; Shuoyang Wang; Guosheng Wang; Qingyang Bi; Reng Zhang; Dong Chen (Journal of Water Process Engineering, 2026)

Neurodevelopmental toxicity induced by iron oxide nanoparticles: Insights from chick and zebrafish embryonic models - Bi-Xia Huang; Tao Zhang; Qing-Bin Dong; Peng-Xing Lin; Yi Zhou; Xin-Shuo Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Semi-anchored percolation networks for low-threshold and selective desalination in FCDI - Lirong Bi; Xinwei Sui; Shuo Tian; Xiaowei Liu; Shicheng Ma; Zhongqiu Liu; Yujing Liu; Anguo Ying (Desalination, 2025)

Boosting power output of NH3BH3 fuel cell by modulating H* and OH− adsorption via Cu@Pd core-shell structured nanowire arrays - Shuo Bi; Libo Zhu; Han Tian; Fantao Kong; Xu Yu; Qin Li; Xiangzhi Cui; Jianlin Shi (Chemical Engineering Journal, 2025)

Lipoprotein-mimicking nanodiscs for precise glioblastoma therapy and immune microenvironment modulation - Taiyu Liu; Lisha Liu; Dandan Gao; Wenqing Li; Xianggui Wu; Shuo Li; Beiyuan Zhang; Yaohua Liu; Qiao Shan; Meiqing Lou; Lifang Yin; Yunke Bi (Chemical Engineering Journal, 2025)

Functional divergence of CAD-like family genes in Saccharum complex under biotic and abiotic stress - Zhu-Qing Wang; Sheng-Ren Sun; Hao-Yu Wang; Zheng-Wang Bi; Hai-Long Chang; Shuo-Hang Zhang; Jun-Lv Chen; Yuan-Xia Qin; Jian-Tao Wu; Wei Zhang; Huan-Ying Xu; San-Ji Gao; et al. (Plant Cell Reports, 2025)

Potential of hyperspectral LiDAR in individual tree segmentation: A comparative study with multispectral LiDAR - Ao Wang; Shuo Shi; Jian Yang; Bowei Zhou; Yi Luo; Xingtao Tang; Jie Du; Sifu Bi; Fangfang Qu; Chengyu Gong; Wei Gong (Urban Forestry & Urban Greening, 2025)

Watt-level power density of direct borohydride fuel cells enabled by electrode local-environment and mass transport regulations - Libo Zhu; Tiantian Wu; Shuo Bi; Changchun Ke; Chang Chen; Han Tian; Fantao Kong; Xiangzhi Cui; Jianlin Shi (Chemical Engineering Journal, 2025)

An optimised molecular-based method for ecological study of tardigrades in soils - Zi-Yang He; Hang-Wei Hu; Keren Wu; Li Bi; Shuo Na; Anthony Weatherley; Michael Nash; Ji-Zheng He (Soil Biology and Biochemistry, 2024)

Identification of key genes of diabetic cardiomyopathy in hiPSCs-CMs based on bioinformatics analysis - Shuo An; Hongchen Bi; Xiaoli Luo; Caiying Zhu; Min Wang; Aiming Pang; Yujie Cui (Molecular and Cellular Biochemistry, 2024)

Monovalent cation exchange membranes prepared by Fe3+-assisted coupled surface modification of PEI-PPy for potassium extraction from simulated brine - Mengmeng Sun; Chenglin Mu; Shuo Wang; Jingtao Bi; Xiaofu Guo; Shizhao Wang; Yingying Zhao (Desalination, 2024)

Regional-scale biogeographical patterns of soil extracellular enzyme activities across eight Chinese fir plantation locations - Han-shuo Zhang; Mi-lin Deng; Hao Yang; Bi-jiang Fang; Wen-feng Lan; Qiu-hua Ma; Huai-feng Weng; Zhi-jie Yang; Yi-rong Zhang; Yong Zheng (European Journal of Soil Biology, 2024)

Amorphous bimetallic-organic framework enable accelerated redox kinetics and polysulfide trapping for lithium-sulfur batteries - Jingkun Bi; Lu Chen; Xiao Yan; Jian Guo; Ya Tang; Ma Jian; Shuo Meng; Kexuan Liao; Jia Yu; Wenli Yao; Ting He; Hongbin Zhao (Chemical Engineering Journal, 2024)

Controlled-diffusion centrifugal microfluidic for rapid antibiotic susceptibility testing - Zheng Pang; Shunji Li; Shangang Wang; Zonglin Cai; Shuo Zhang; Chao Wan; Jieqing Wang; Yiwei Li; Peng Chen; Bi-Feng Liu (Analytica Chimica Acta, 2024)

Effects of phytohormone on Chlorella vulgaris grown in wastewater-flue gas: C/N/S fixation, wastewater treatment and metabolome analysis - Wenwen Kong; Shilin Shi; Denghui Peng; Shuo Feng; Lianfei Xu; Xin Wang; Boxiong Shen; Yonghong Bi; Honghong Lyu (Chemosphere, 2023)

Highly conductive and tough polyacrylamide/sodium alginate hydrogel with uniformly distributed polypyrrole nanospheres for wearable strain sensors - Yansong Zhang; Shuo Li; Zhongda Gao; Dejin Bi; Na Qu; Sanqing Huang; Xueqin Zhao; Renhong Li (Carbohydrate Polymers, 2023)

Aircraft observation of fast initiation of mixed phase precipitation in convective cloud over the Tibetan Plateau - Delong Zhao; Minghuai Wang; Daniel Rosenfeld; Baojun Chen; Dantong Liu; Xuexu Wu; Kang Hu; Shuo Ding; Yannian Zhu; Yi Zeng; Yi Qu; Yang Gao; et al. (Atmospheric Research, 2023)

Transient Receptor Potential Vanilloid 4: a Double-Edged Sword in the Central Nervous System - Meng-liu Zeng; Shuo Kong; Tao-xiang Chen; Bi-wen Peng (Molecular Neurobiology, 2023)

Migration and abiotic transformation of estrone (E1) and estrone-3-sulfate (E1-3S) during soil column transport - Banghao Du; Weiwei Yu; Lun Yang; Gongduan Fan; Shuo Yang; Hui Jiang; Shenglan Bi; Cheng Yu (Environmental Geochemistry and Health, 2022)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Typhoon frequency sequence reconstruction and characteristics analysis in the Southeast Coastal Area over China during the Ming and Qing dynasties - Li Sun; Shuo-ben Bi; Chang-chun Chen; Feng Zhao; Ying Lu (Natural Hazards, 2020)

High-efficient n-butanol production by co-culturing Clostridium acetobutylicum and Saccharomyces cerevisiae integrated with butyrate fermentative supernatant addition - Hongzhen Luo; Qingwei Zeng; Shuo Han; Zhaoyu Wang; Qing Dong; Yanhong Bi; Yuping Zhao (World Journal of Microbiology and Biotechnology, 2017)

Axonal regeneration in early stages of sciatic nerve crush injury is enhanced by α7nAChR in rats - Dewei Wang; Xuming Wang; Shuo Geng; Zhenggang Bi (Molecular Biology Reports, 2015)